Studi Potensi Talas Liar sebagai Sumber Bioetanol dan Implementasinya pada Pembelajaran Biologi - Herlina Herlina; Aceng Ruyani; Zamzaili Zamzaili; Budiyanto Budiyanto (PendIPA Journal of Science Education, 2019)
ABSTRACT[Study of Potential of Wild Taro as a Bioethanol Source and Its Implementation in Biological Learning]. This research aims to (1) Determine the carbohydrate content in three types of wild taro. (2) Assessing the effect of different types of yeast on ethanol produced. (3) Assessing the effect of fresh and dried taro tubers on ethanol produced. (4) To find out the difference in learning outcomes of students who use research-based LKS and those who do not use research-based LKS. Bioethanol is obtained through fermentation using yeast. The method used is direct observation and testing of the bioethanol produced. The carbohydrate content of taro kembaang (Colocasia esculenta) in wet conditions is 23.04% and in dry conditions 78.433%. For kemumu forest (Alocasia macrorrhiza) in wet conditions 20.08% and in dry conditions 79,725. For black taro (Xantomonas nigrum) 23.20% in wet conditions and in dry conditions 72.622%. Traditional yeast produces more ethanol than packaging yeast (Fermipan). More ethanol is produced in taro in dry conditions, namely kembaang taro (Colocasia esculenta) 2.30%, kemumu taro forest (Alocasia macrorrhiza) 2.64% and black taro (Xantomonas nigrum) 2.23%. Based on the fresh dried taro tuber, dried taro tubers produce more ethanol. LKS which is a learning resource is used to determine whether there is a difference between the experimental class and the control class using the T test. There are significant differences in learning outcomes between the experimental classes using research-based LKS and the control class that does not use research-based LKS which is characterized by the T test test where th> tk, th = 18.3138 and tk = 2.0085. So that the experimental class learning outcomes are better than the control class. Keywords: Potential; wild taro; bioethanol; learning process.(Received November 6, 2018; Accepted February 9, 2019; Published February 26, 2019) ABSTRAKPenelitan ini bertujuan untuk (1) menentukan kandungan karbohidrat pada tiga jenis talas liar. (2) Mengkaji pengaruh perbedaan jenis ragi terhadap etanol yang dihasilkan. (3) Mengkaji  pengaruh segar dan keringnya umbi talas terhadap etanol yang dihasilkan. (4) Untuk mengetahui perbedaan hasil belajar siswa yang menggunakan LKS berbasis riset dan yang tidak menggunakan LKS berbasis riset. Bioetanol didapatkan melalui fermentasi menggunakan ragi.Kandungan karbohidrat talas kembaang (Colocasia esculenta) pada kondisi basah 23.04% dan pada kondisi kering 78.433%. Untuk talas kemumu hutan (Alocasia macrorrhiza) pada kondisi basah 20.08% dan pada kondisi kering 79.725. Untuk talas hitam (Xantomonas nigrum) 23.20% pada kondisi basah dan pada kondisi kering 72.622%. Ragi tradisional lebih banyak  menghasilkan etanol  dari pada ragi kemasan (Fermipan). Etanol lebih banyak dihasilkan pada talas dalam kondisi kering yaitu talas kembaang (Colocasia esculenta) 2.30%, talas kemumu hutan (Alocasia macrorrhiza) 2.64% dan talas hitam (Xantomonas nigrum) 2.23%. Berdasarkan segar keringnya umbi talas, umbi talas kering lebih banyak menghasilkan etanol. LKS yang merupakan sumber belajar digunakan untuk mengetahui ada tidaknya perbedaan antara kelas eksperimen dan kelas kontrol dengan menggunakan uji T. Terdapat perbedaan hasil belajar yang signifikan antara kelas eksperimen yang menggunakan LKS berbasis riset dan kelas kontrol yang tidak menggunakan LKS berbasis riset yang ditandai dengan uji T tes dimana th>tk, th = 18.3138 dan tk = 2.0085. Sehingga hasil belajar kelas eksperimen lebih baik dari pada kelas kontrol. Kata kunci: Potensi; talas liar; bioetanol; pembelajaran.